Dynamic Response of Flexible Wind Turbine Blade - Yu-qiao Zheng; Rong-zhen ZHAO; Hong liu (Institute of Advanced Engineering and Science, 2013)
Aiming at the non-stationary and stall flutter problems of wind turbine blade caused by transient load fluctuations, the dynamic properties of wind turbine were studied, the blade was simplify to a cantilever beam in case of the action of shear deformation and cross section rotating effect were considered in this analysis, equations of the blade were established based on D'Alemberts' principle and the principle of virtual displacement. The dynamic response of the wind turbine was solved by using the finite element method under the transient load environment. A 29.2 m rotor blade, previously reported in specialized literature, was chosen as a case study to validate dynamic behaviour predicted by a Timoshenko beam model. It is concluded that despite its simplicity, The cross-sectional shear-deformation has great influence on dynamic response of the blade.Dynamic model is sufficiently accurate to serve as a design tool for the recursive analyses required during design and optimization stages of wind turbines using only readily available computational tools. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3329